Pelatihan Teknik Pengajaran Vocabulary Berbasis Media Realia bagi Guru TK Bakti Sesela Kabupaten Lombok Barat - Tri Setianingsih; Bq Zuhrotun Nafisah; M A Rizka; Sri Ariani; I Made Permadi Utama; Siti Syafiatul Qomariyah; Imansyah Imansyah (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2021)
The purpose of this community service activity is to improve the understanding and ability of teachers at TK Bakti, Sesela, in applying vocabulary teaching techniques based on realia media. This is based on the lack of ability of teachers at TK Bakti in teaching vocabulary material to the children. The method used in the implementation of this service is participatory training with a duration of activities for one month as the scheduled basis. There were five students involved in this program. The results of this community service activity were the teachers at TK Bakti, Sesela had the understanding and ability to apply realia media for vocabulary teaching techniques. In addition, it can make the teachers easier to teach English to students by using objects in the surrounding environment without having to buy new media or toys that are expensive, so they can also save school expenses with limited funds. This community service activity also really helps to make the students easier to remember vocabulary in English as a basic for their ability to speak English in the future.